Periodontitis Exacerbates Benign Prostatic Hyperplasia through Regulation of Oxidative Stress and Inflammation. (18th October 2021) - Fang, Cheng; Wu, Lan; Zhao, Ming-Juan; Deng, Tong; Gu, Jia-Min; Guo, Xing-Pei; Li, Cheng; Li, Weiguang; Zeng, Xian-Tao
Abstract : Epidemiological studies demonstrate that men with periodontitis are also susceptible to benign prostatic hyperplasia (BPH) and that periodontal treatment can improve the prostatic symptom. However, molecular links of this relationship are largely unknown. The goal of the current study was to elucidate the effects of experimental periodontitis on the hyperplasia of prostate and whether oxidative stress and inflammation participated in this process. For this purpose, ligature-induced periodontitis, testosterone-induced BPH, and the composite models in rats were established. Four weeks later, all the rats were sacrificed and the following items were measured: alveolar bone loss and histological examination of periodontal tissues were taken to assess the establishment of periodontitis model, prostate index and histological examination of prostate tissues were taken to test the establishment of the BPH model, inflammatory cytokines in plasma were assessed, and Bax/Bcl-2 proteins related to cell apoptosis were analyzed via western blot analysis. To further investigate whether oxidative stress participates in the aggravation of BPH, in vitro models were also conducted to measure the production of intracellular reactive oxygen species (ROS) and hydrogen peroxide (H2 O2 ) concentration. We found that simultaneous periodontitis and BPH synergistically aggravated prostate histological changes, significantly increased Ki67 proliferation, and reduced apoptosis in rat prostate tissues. Also, our results showed that periodontal ligation induced increased Bcl-2 protein expression, whereas Bax expression was decreased in BPH rats than in normal rats. Compared with the control group, periodontitis and BPH both significantly enhanced inflammatory cytokine levels of TNF- α, IL-6, IL-1 β, and CRP. Furthermore, Porphyromonas gingivalis lipopolysaccharide induced enhanced generation of intracellular expression of ROS and H2 O2 in BPH-1 cells. Our experimental evidence demonstrated that periodontitis might promote BPH development through regulation of oxidative stress and inflammatory process, thus providing new strategies for prevention and treatment of BPH.